1989
DOI: 10.1002/bjs.1800760512
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of body water compartments after ligation of the common bile duct in the rabbit

Abstract: To elucidate the pathogenesis of renal insufficiency associated with obstructive jaundice we have studied spontaneous water intake and body water compartments in rabbits undergoing common bile duct ligation. Total body water, extracellular water and plasma volume were measured by multi-isotope dilution technique. During the initial 6 postoperative days spontaneous water intake was 898 ml in sham operated animals (SO) but only 280 ml in jaundiced rabbits (OJ6) (P less than 0.01). Creatinine clearance was almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 11 publications
1
7
0
3
Order By: Relevance
“…Previous studies have shown that patients with obstructive jaundice present with haemodynamic and body fluid disturbances3–5, the most relevant of which are ECW depletion, depressed myocardial function, and increased plasma levels of ANP and water‐ and sodium‐retaining hormones9–12. In the present study a significant decrease in the ECW compartment was noted in patients with both benign and malignant obstructive jaundice, with volume depletion averaging 3–4 per cent of bodyweight (2000 ml in men and 1800 ml in women).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown that patients with obstructive jaundice present with haemodynamic and body fluid disturbances3–5, the most relevant of which are ECW depletion, depressed myocardial function, and increased plasma levels of ANP and water‐ and sodium‐retaining hormones9–12. In the present study a significant decrease in the ECW compartment was noted in patients with both benign and malignant obstructive jaundice, with volume depletion averaging 3–4 per cent of bodyweight (2000 ml in men and 1800 ml in women).…”
Section: Discussionsupporting
confidence: 65%
“…Experimental and human studies6–8 have demonstrated that obstruction of the biliary tract is associated with raised plasma concentrations of atrial natriuretic peptide (ANP). This occurs despite the fact that moderate to marked volume depletion is a hallmark of obstructive jaundice, as shown by tracer dilution techniques9, 10, bioelectric impedance analysis11 and endocrine markers12. This paradoxical increase in ANP is accompanied by increased aldosterone and plasma renin activity and might indicate that this hormone plays a direct role in the pathogenesis of renal dysfunction8.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proposed that patients with obstructive jaundice present with hemodynamic and body fluid disturbances [23][24][25]. Our group also demonstrated that extracellular water volume was reduced in the presence of obstructive jaundice [6,7]. Both studies were performed using the same multiisotope dilution technique.…”
Section: Discussionmentioning
confidence: 77%
“…The precise etiology of renal dysfunction in such patients remains elusive [2]. Hemodynamic and body fluid disturbances, have been proposed as the final common pathway [3][4][5].In an experimental study, rabbits with common bile duct ligation experienced a reduction in the extracellular water compartment (ECW) and plasma volume [6]. Only one comprehensive clinical study [7] has been carried out to determine the body water compartment status in patients with obstructive jaundice.…”
mentioning
confidence: 99%
“…More recently, this work has been corroborated using multi-isotope dilution techniques to study the fluid compartments within the body. Martinez-R6denas et al 63, using a rabbit bile duct ligation model, observed an initial reduction in the overall volume of extracellular fluid followed by a 15 per cent fall in the plasma volume. These changes wcrc associated with hypodipsia, hypophagia and an impaired ability to concentrate urine.…”
Section: The Role Of Prostaglandinsmentioning
confidence: 98%